Structural and magnetic properties of nickel nanowires grown in porous anodic aluminium oxide template by electrochemical deposition technique. (28th March 2018) - Pratama, Sendi Nugraha; Kurniawan, Yudhi; Muhammady, Shibghatullah; Takase, Kouichi; Darma, Yudi
Abstract: We study the formation of nickel nanowires (Ni NWs) grown in porous anodic aluminium oxide (AAO) template by the electrochemical deposition technique. Here, the initial AAO template was grown by anodization of aluminium substrate in sulphuric acid solution. The cross-section, crystal structure, and magnetic properties of Ni NWs system were characterized by field-emission SEM, XRD, and SQUID. As a result, the highly-ordered Ni NWs are observed with the uniform diameter of 27 nm and the length from 31 to 163 nm. Based on XRD spectra analysis, Ni NWs have the face-centered cubic structure with the lattice parameter of 0.35 nm and average crystallite size of 17.19 nm. From SQUID measurement at room temperature, by maintaining the magnetic field perpendicular to Ni NWs axis, the magnetic hysteresis of Ni NWs system show the strong ferromagnetism with the coercivity and remanence ratio of ∼148 Oe and ∼0.23, respectively. The magnetic properties are also calculated by means of generalized gradient approximation methods. From the calculation result, we show that the ferromagnetism behavior comes from Ni NWs without any contribution from AAO template or the substrate. This study opens the potential application of Ni NWs system for novel functional magnetic devices.